2021
DOI: 10.3390/bioengineering8090120
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of the Third Molar: A Therapeutic Alternative to the Rehabilitation of a Missing Tooth: A Scoping Review

Abstract: Introduction: Tooth autotransplantation is the repositioning of an erupted, partially erupted, or non-erupted autologous tooth from one site to another within the same individual. Several factors influence the success rate of the autotransplant, such as the stage of root development, the morphology of the tooth, the surgical procedure selected, the extraoral time, the shape of the recipient socket, the vascularity of the recipient bed, and the vitality of the cells of the periodontal ligament. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 107 publications
0
21
0
1
Order By: Relevance
“…Adequate bony support may not be present in some cases due to various reasons such as tooth aplasia or its early loss. Alveolar ridge resorption and root protrusion through dehiscence may occur in cases of insufficient bony support, so the use of free bone autografts in these cases is highly recommended [4].…”
Section: Recipient Site Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Adequate bony support may not be present in some cases due to various reasons such as tooth aplasia or its early loss. Alveolar ridge resorption and root protrusion through dehiscence may occur in cases of insufficient bony support, so the use of free bone autografts in these cases is highly recommended [4].…”
Section: Recipient Site Criteriamentioning
confidence: 99%
“…The donor tooth should be atraumatically extracted to preserve and minimize the damage to the periodontal ligaments around the tooth [1,4], as one of the most important factors that affect the success of a transplanted tooth is the viability of periodontal ligaments [4,5,34]; these contain cells that have the potential to differentiate into cementoblasts, osteoblasts, and fibroblasts, and they have an important role in tissue regeneration [4]. Several studies have indicated that donor teeth with atrophic periodontal ligaments can be easily damaged and have a higher risk of complications [15,28,34].…”
Section: Donor Tooth Criteriamentioning
confidence: 99%
See 3 more Smart Citations